2013
DOI: 10.5888/pcd10.120249
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs and Communication Practices Regarding Cognitive Functioning Among Consumers and Primary Care Providers in the United States, 2009

Abstract: IntroductionLimited research has examined primary care providers’ communication with patients about maintaining cognitive functioning. Our study’s objective was to compare the perceptions of consumers and primary care providers related to beliefs and communication practices about lifestyle behaviors beneficial for overall health and for maintaining cognitive functioning.MethodsIn 2009, we submitted 10 questions to Porter Novelli’s HealthStyles survey and 6 questions to their DocStyles survey. We compared consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 22 publications
1
25
0
Order By: Relevance
“…An analysis of the Porter Novelli Health Styles survey data indicated that close to 30 % of consumers have searched specifically for cognition and AD-related information online [14]. Findings from the Health Information National Trends Survey (HINTS) for Puerto Rico showed that nearly 60 % of respondents used the Internet as their primary source of health information [15].…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of the Porter Novelli Health Styles survey data indicated that close to 30 % of consumers have searched specifically for cognition and AD-related information online [14]. Findings from the Health Information National Trends Survey (HINTS) for Puerto Rico showed that nearly 60 % of respondents used the Internet as their primary source of health information [15].…”
Section: Introductionmentioning
confidence: 99%
“…Participants were asked whether they thought that physical activity (exercising and being physically active) could reduce the risk of dementia and selected one choice from "strongly disagree," "somewhat disagree," "somewhat agree," and "strongly agree." Previous studies (Ayalon, 2013;Friedman et al, 2013) have employed a single-item method to evaluate the expectation for physical activity to minimize dementia risk. Cancer studies (Coups, Hay, & Ford, 2008;Miyawaki, Shibata, Ishii, & Oka, 2014) have also measured the expectation for physical activity to reduce cancer risk using a single item.…”
Section: Methodsmentioning
confidence: 99%
“…In the research area of cancer, previous studies have also suggested that exposure to information about the role of exercise in cancer prevention could increase exercise motivation among university students (Courneya & Hellsten, 2001), general adults (Graham, Prapavessis, & Cameron, 2006), and adults with higher cancer risk (McGowan & Prapavessis, 2010). In the research area of dementia, although population-based studies have examined which and how many people expected physical activity to minimize dementia risk (Ayalon, 2013;Friedman et al, 2013;Low & Anstey, 2009;Smith, Ali, & Quach, 2014), it remains unclear whether the expectation about it is related to physical activity level. If the expectation for physical activity to minimize dementia risk influences physical activity engagement in older adults, it suggests that increasing expectation about this effect would promote physical activity among this population.…”
mentioning
confidence: 99%
“…Maintaining cognitive health and preventing age‐related cognitive decline in older adults is a public health priority . Older adults want to preserve their cognitive abilities as they age; losing cognitive abilities is among the most feared consequences of aging . Risk of cognitive decline increases significantly with age .…”
Section: Theoretical Definitions For Six Dimensions Of Wellnessmentioning
confidence: 99%